Extraction Process Optimization of Flavonoids from Lycium barbarum Root and Its Antioxidant and Hypoglycemic Activities in Vitro - Jiayi WEI; Lu LU; Lutao ZHANG; Bo JIN; Haoqi NING; Yanping LI; Jia MI; Yamei YAN (Shipin gongye ke-ji)
To investigate the extraction process of flavonoids from Lycium barbarum roots, this study utilized Lycium barbarum roots as the source material and employed an orthogonal experimental design. The optimization of the ethanol extraction method for Lycium barbarum root flavonoids was based on the total flavonoid content. The study also explored the in vitro antioxidant and blood glucose-lowering activities of the Lycium barbarum root extract. The results indicated that the optimal extraction process for Lycium barbarum root flavonoids included a water bath temperature of 60 ℃, an ethanol concentration of 80%, the addition of 0.75% cellulase, and a water bath duration of 90 min. At these conditions, the Lycium barbarum root extract produced the maximum total flavonoid content, reaching 103.61±0.08 mg/g. The Lycium barbarum root extract demonstrated IC50 values of 0.09 mg/mL and 1.06 mg/mL for scavenging DPPH and ABTS+ free radicals, respectively. Additionally, the IC50 values for inhibiting α-amylase and α-glucosidase were 7.27 mg/mL and 19.35 mg/mL, respectively, providing impressive in vitro antioxidant and blood glucose-lowering activities.